CAD/CAM Theory and Practice - Zeid, Ibrahim ([S.l.] : McGraw-Hill Science/Engineering/Math, 2013)
This text is suitable for an introduction to CAD/CAM taught in departments of mechanical engineering. The book combines a good balance of the three main ingredients of CAD/CAM: computer science, engineering design and applications, and industrial implementations and technology.
Keywords: CAD/CAM systems